TINGKAT KECERDASAN EMOSIONAL SISWA MTS S ADAT DAN SYARA’ NAGARI MATUR MUDIAK KECAMATAN MATUR KABUPATEN AGAM - Prisma Winda; Afrinaldi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. The research carried out aims to describe the level of emotional intelligence of MTs S Adat and Syara' students. The research is quantitative with a descriptive nature. The population studied included all MTs S Adat and Syara' students totaling 92 students. The sample studied was 92 students, taken using a total sampling technique. To collect data, researchers used a questionnaire instrument with a Likert scale type. The results of this research show that in general the level of emotional intelligence of students in each dimension, namely Recognizing one's emotions, Managing emotions, Motivating oneself, Recognizing other people's emotions, and Building relationships in the research sample, the majority of students have poor emotional intelligence abilities with an overall low category of 57.61 % with a total of 53 students.